1978
DOI: 10.1021/ja00472a032
|View full text |Cite
|
Sign up to set email alerts
|

Organic sulfur chemistry. 26. Synthesis and reactions of some new sulfur transfer reagents

Abstract: Six new azole sulfur transfer reagents have been prepared from their trimethylsilyl derivatives and SxCl2 (x = 1,2) The reactions of these reagents are different from those of SCla or the corresponding phthalimide reagent with thiols, amines, and alcohols. A possible mechanism is discussed. Of particular interest is the facile, high-yield formation of sultines 21 and 22 with the monosulfur azole reagent, MA'-thiobisbenzimidazole (6a).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
0
3

Year Published

1983
1983
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(56 citation statements)
references
References 3 publications
0
53
0
3
Order By: Relevance
“…Durch Einsatz von silylierten sekundaren Aminen l a -c konnten mit Schwefeldichlorid (2) jedoch unter schonenderen, selektiveren Synthesebedingungen die substituierten Sulfoxylsaure-diamide 3a -c bei gemairjigten Reaktionstemperaturen 19,20) erhalten werden; andererseits konnte das jeweils entstandene Chlortrimethylsilan leicht entferrit werden -im Gegensatz zu den oft sehr schwierig abzutrennenden Alkylammoniumchloriden. Die ersten N,N'-bis-silylierten Sulfoxylsaure-diamide (,,Diaminosulfane") wurden von Rinne und Mitarbb. 21*22) sowie von uns3) dargestellt.…”
Section: Die Ersten Vertreter Der Sulfoxylsaure-diamide Wurden Von MIunclassified
“…Durch Einsatz von silylierten sekundaren Aminen l a -c konnten mit Schwefeldichlorid (2) jedoch unter schonenderen, selektiveren Synthesebedingungen die substituierten Sulfoxylsaure-diamide 3a -c bei gemairjigten Reaktionstemperaturen 19,20) erhalten werden; andererseits konnte das jeweils entstandene Chlortrimethylsilan leicht entferrit werden -im Gegensatz zu den oft sehr schwierig abzutrennenden Alkylammoniumchloriden. Die ersten N,N'-bis-silylierten Sulfoxylsaure-diamide (,,Diaminosulfane") wurden von Rinne und Mitarbb. 21*22) sowie von uns3) dargestellt.…”
Section: Die Ersten Vertreter Der Sulfoxylsaure-diamide Wurden Von MIunclassified
“…Herein, we report the preparation of the five-membered cyclic thionosulfite 4 by treatment of cis-3,4-di-(tert-butyl)tetrahydrothiophene-3,4-diol (5) [9] with 1,1'-thiobis(1H-benzimidazole) (6) [10], and the isolation of the two diastereoisomers 4a and 4b (see Scheme 1 below) 2 ). The structures of 4a and 4b are discussed on the basis of X-ray crystallographic analyses, spectral data, and density functional theory (DFT) calculations.…”
mentioning
confidence: 99%
“…Previously, Harpp et al showed that thionosulfites are produced from 1,2-diols by treatment with 6 [10]. We applied this method to 5 to obtain 4 directly [4a] (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of bis-benzimidazolyl sulfide 9 with 2,2'-bis-(hydroxymethy1)biphenyl 10 inserts the sulfur between the oxygens to form the cyclic sulfoxylate ester 11 which is sometimes isolable, often depending on the a-substituents (6,7). This cyclic sulfoxylate thermally rearranges to the thermodynamically more stable cyclic sulfinate ester 12 and eventually to the stable sulfone 13.…”
mentioning
confidence: 99%